Searching for a dipole modulation in the large-scale structure of the Universe. Issue 3 (20th May 2014) - Fernández-Cobos, R.; Vielva, P.; Pietrobon, D.; Balbi, A.; Martínez-González, E.; Barreiro, R. B.
Abstract : Several statistical anomalies in the cosmic microwave background (CMB) temperature anisotropies seem to defy the assumption of a homogeneous and isotropic universe. In particular, a dipole modulation has been detected both in WMAP and Planck data. We adapt the methodology proposed by Eriksen et al. on CMB data to galaxy surveys, tracing the large-scale structure. We analyse the National Radio Astronomy Observatory (NRAO) and Very Large Array (VLA) Sky Survey data at a resolution of ∼2° for three different flux thresholds: 2.5, 5.0 and 10.0 mJy, respectively. No evidence of a dipole modulation is found. This result suggests that the origin of the dipole asymmetry found in the CMB cannot be assigned to secondary anisotropies produced at redshifts around z  = 1. However, it could still have been generated at redshifts higher or lower, such as the integrated Sachs–Wolfe effect produced by the local structures. Other all-sky surveys, like the infrared WISE catalogue, could help to explore with a high sensitivity a redshift interval closer than the one probed with NVSS.